Perkembangan Kesenian Tradisional Calung Renteng di Kecamatan Cibaliung Kabupaten Pandeglang Provinsi Banten - Emah; Ana Nurhasanah; Yuni Maryuni (PANALUNGTIK, 2023)
The traditional art of Calung Renteng Cibaliung is the only traditional calung art that is still very traditional with very simple musical instruments, but can survive to this day in the midst of technological developments and modernization that occur in society. The traditional art of Calung Renteng Cibaliung as a traditional art must be preserved, because in addition to the heritage from the ancestors, it is also a traditional music that is full of aesthetic value. This research aims to find out the development of Calung Renteng Traditional Arts in Cibaliung District, Pandeglang Regency. The research method is the historical method, which includes heuristic (collection of sources), source criticism, interpretation, and historiography. The community in Cibaliung District created calung renteng as a traditional art that functions to eliminate boredom and boredom while waiting for rice. The beginning of the emergence of the art of calung renteng is not known for sure, but it has appeared since the 1990s. The art of calung renteng experienced rapid development in 2003-2020. Previously, the art of calung renteng was only played in huma. However, after being inaugurated as a typical art, the calung renteng changed its function to become a folk performing art, which is displayed in events organized by the community and the government. This shows that there is a change in function that occurs in the art of calung renteng. This change also makes the art of calung renteng not extinct because it adapts to the movement of the times that continue to change.